2022
DOI: 10.1055/s-0042-1743173
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dual-Energy Computed Tomography in Gallbladder Disease: A Review

Abstract: Gallbladder diseases are common and include a spectrum ranging from benign to cancer. Imaging plays an integral role in the diagnosis and in guiding appropriate management. While most patients with gallstone (GS) diseases can be evaluated with ultrasound, those with complicated GS disease, suspicion of cancer, or staging of cancer need additional cross-sectional imaging. Computed tomography (CT) is widely available and is often the imaging test of choice following an equivocal ultrasound or negative ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a recent systematic review, the US features of benign and malignant gallbladder wall thickening were reported [69]. A few novel imaging techniques, including DECT and texture analysis, have recently been investigated to increase the accuracy of detection of malignant gallbladder wall thickening [70][71][72]. Additionally, a gallbladder reporting and data system (GB-RADS) has been proposed to stratify the risk of malignant gallbladder wall thickening in US [73].…”
Section: Differentiating Benign From Malignant Gallbladder Wall Thick...mentioning
confidence: 99%
“…In a recent systematic review, the US features of benign and malignant gallbladder wall thickening were reported [69]. A few novel imaging techniques, including DECT and texture analysis, have recently been investigated to increase the accuracy of detection of malignant gallbladder wall thickening [70][71][72]. Additionally, a gallbladder reporting and data system (GB-RADS) has been proposed to stratify the risk of malignant gallbladder wall thickening in US [73].…”
Section: Differentiating Benign From Malignant Gallbladder Wall Thick...mentioning
confidence: 99%
“…In this context, dual-energy CT (DECT) has been proven to be a highly accurate method for tumor assessment due to its shown improved material characterization and differentiation compared to conventional single-energy CT [14,15]. In this context, DECT postprocessing provides a variety of additional quantitative parameters of tumor characteristics, including atomic number maps (Rho/Z) showing the Rho and Z of lesions [16,17]. Numerous studies have assessed DECT advantages, especially in oncology [14,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the following article, Marri and Madhusudhan 3 have explained the role of DECT in the evaluation of diffuse liver diseases like fat/iron deposition and fibrosis. In the subsequent article, Singh et al 4 have discussed the use of DECT in evaluating gall bladder pathologies. Further in the issue, Mroueh et al 5 have explained the role of DECT in pancreas imaging with applications in pathologies like pancreatitis, trauma, and pancreatic neoplasms.…”
mentioning
confidence: 99%